Group Investigation Method Improves Breast Self-Examination Behavior in Women of Childbearing Age - Sella Dwi Oktaviani; Agung Riyadi; Epti Yorita; Desi Widiyanti; Sri Yanniarti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Breast cancer is one of the most common types of cancer suffered by women worldwide with a high incidence rate. The increasing number of new cases that appear every year will be a threat, This study aims to determine how the influence of Group Investigation on increasing knowledge, attitudes and actions of women of childbearing age towards BSE. This type of research is quasy experiment designs with nonequivalent control group design. The intervention group was given education with the Group Investigation method, the control group with the jigsaw method. The number of samples used was 52 people, 26 for the intervention group and 26 for the control group taken by proportionate stratified random sampling technique. The results of the Wilcoxon test found that education with the group investigation method has an influence on knowledge with value (p-value = 0.000), attitude (p-value = 0.000) and action (p-value = 0.000). The test results also showed that there was an influence of the jigsaw method on knowledge with values (p-value = 0.000), attitudes (p-value = 0.000) and actions (p-value = 0.000). The results of the mann-whitney test found that the group investigation method was more effective for increasing knowledge (p-value = 0.000), attitudes (p-value = 0.000) and WUS Actions (p-value = 0.590) about BSE compared to the Jigsaw method. The conclusion of this study is that group investigation method is effective in improving breast self- examination behavior in women of childbearing age.